Evaluation of DELTA PREP: A Project Aimed at Integrating Primary Prevention of Intimate Partner Violence Within State Domestic Violence Coalitions. (August 2015) - Freire, Kimberley E.; Zakocs, Ronda; Le, Brenda; Hill, Jessica A.; Brown, Pamela; Wheaton, Jocelyn
Background. Intimate partner violence (IPV) has been recognized as a public health problem since the late 20th century. To spur IPV prevention efforts nationwide, the DELTA PREP Project selected 19 state domestic violence coalitions to build organizational prevention capacity and catalyze IPV primary prevention strategies within their states. Objective. DELTA PREP's summative evaluation addressed four major questions: (1) Did coalitions improve their prevention capacity during the project period? (2) Did coalitions serve as catalysts for prevention activities within their states during the project period? (3) Was initial prevention capacity associated with the number of prevention activity types initiated by coalitions by the end of the project? (4) Did coalitions sustain their prevention activities 6 months after the end of the project period? Results. DELTA PREP achieved its capacity-building goal, with all 19 participant coalitions integrating prevention within their organizations and serving as catalysts for prevention activities in their states. At 6 months follow up, coalitions had sustained almost all prevention activities they initiated during the project. Baseline prevention capacity (Beginner vs. Intermediate) was not associated with the number of prevention activity types coalitions implemented by the end of the project. Conclusion. Service and treatment organizations are increasingly asked to integrate a full spectrum of prevention strategies. Selecting organizations that have high levels of general capacity and readiness for an innovation like integrating a public health approach to IPV prevention will likely increase success in building an innovation-specific capacity, and in turn implementing an innovation.